Application of Organic Fertilizer Pellets from Egg Shell Waste in Spinach (Amaranthus hybridus L): Aplikasi Pupuk Organik Pelet dari Limbah Kulit Telur pada Tanaman Bayam (Amaranthus hybridus L) - Haryanta, Dwi; Venia, Venia; Saadah, Tatuk Tojibatus (Journal of Applied Plant Technology, 2023)
Egg shells are household waste that is very easy to find. Egg shells or egg shells can also come from waste disposal of laying hens. So far, there is a lot of egg shell waste by martabak sellers in Surabaya. The lack of public knowledge and insight regarding the use of eggshell waste causes this waste to pollute the environment. This study aims to determine the interaction between the application of organic fertilizer eggshell waste pellets and the dose of urea fertilizer used and its effect on the growth and yield of spinach plants. This research was conducted from mey to june 2022 at the Experimental Garden of the Faculty of Agriculture, Wijaya Kusuma University, Surabaya. This experiment was carried out using a randomized block design consisting of two treatment factors, namely POPe of eggshell waste (P) and dose of urea (K). This treatment was repeated three times with P0 (without POPe treatment), POPe treatment of eggshell waste consisting of P1 (9 gr POPe), P2 (18 gr POPe), P3 (27 gr POPe) and K0 (without urea dose), dose urea K1 fertilization (3.2 gr urea). The results showed that the use of POPe and urea on spinach plants had no significant effect on any observed parameters.